A comunicação em fóruns de um curso a distância de formação de professores para uso de TDICS: análise da presença de ensino - Rozenfeld, Cibele Cecílio de Faria [UNESP]; Veloso, Fernanda Silva (My University, 2014)
The importance of the inclusion of digital technology in the classroom has already been pointed out by numerous authors in the educational field and some of them herald that it is through this inclusion that we can achieve transformations in school settings. Based on this assumption, this paper aims to present a distance learning course offered to in service and preservice teachers, focused on the use of technology in foreign language classroom primarily focusing on the role of teacher educators in mediating discussions. For this we sought theoretical support in studies which deal with distance courses (KENSKI, 2008), about virtual environments (ARAÚJO and MARQUESI, 2008), online discussion forums and investigation community and teaching presence (GARRISON, ANDERSON and ARCHER, 2000). Based on the previous theories presented, teacher educator’s messages were analyzed during a distance course offered to teachers in continuing and initial training, identifying marks of teaching presence and pointing to appropriate mediations and/or possible gaps. The results indicate that the teacher must be even more aware of the types of feedback that are provided and of the teaching presence mentioned by Garrison and colleagues (2000, 2001).

A importância de inclusão de tecnologia digitais em sala de aula já vem sendo apontada por inúmeros autores no campo da educação e alguns deles preconizam que é por meio dessa inclusão que poderemos alcançar transformações em contextos escolares. Partindo desse pressuposto, este trabalho tem como objetivo apresentar um curso a distância oferecido para professores em formação continuada e inicial, voltado para o uso de tecnologias em sala de aula de língua estrangeira focalizando prioritariamente o papel dos professores formadores na mediação das discussões. Para tanto buscamos respaldo teórico em estudos que versam sobre cursos a distância (KENSKI, 2008), sobre ambientes virtuais (ARAÚJO JR.; MARQUESI, 2008), fóruns de discussão online e sobre comunidade de investigação e a presença de ensino (GARRISON; ANDERSON; ARCHER, 2000). Com respaldo nas teorias apresentadas, foram analisadas mensagens dos professores formadores ao longo de um curso oferecido na modalidade a distância para professores em formação continuada e inicial, identificando as marcas da presença de ensino e apontando para as mediações adequadas e/ou possíveis lacunas. Os resultados apontam que o professor deve estar cada vez mais atento aos tipos de feedbacks que fornece e à presença de ensino no sentido de Garrison e colaboradores (2000, 2001).
Forum communication in a distance preservice and in-service teacher education for the use of digital technologies of information and communication: analyses of teaching presence
Keywords: Distance education; Online forums; Teacher education; Educação à distância; Fóruns online; Formação de professores